Review of Efficient Use of Inpatient Beds based on Indicators Barber-Johnson Graph at Anna Medika General Hospital Madura - Rulisiana Widodo (NHM PRESS, 1970)
Hospital statistics are health statistics that use and process data sources from health services, where hospital statistics focus on services in inpatient units. One of the problems in hospitals is that the efficiency of the use of beds is still low, to assess the efficiency of hospitals, Barber-Johnson charts can be used. This study aims to describe the use of inpatient beds at Anna Medika Madura Hospital in the first and second quarter periods of 2018. This type of research is a qualitative research with a descriptive approach. Methods of collecting data using in depth interviews. The results of the study revealed that the efficiency of the use of beds for inpatient care at Anna Medika Madura Hospital was not efficient, due to several factors from internal and external.